SÍNTESE E CARACTERIZAÇÃO DE ESPUMAS VÍTREAS CONTENDO TiO2 E UTILIZANDO HIDRÓXIDO DE SÓDIO COMO AGENTE ESPUMANTE - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
In this work, the effect of sodium hydroxide as a glass foaming agent using glass waste in the foam formulation was performed. During the synthesis process, the variation of temperature, heating rate and sintering time was investigated. Sample density and average pore sizes were estimated using mercury porosimetry. The morphology of the glass foams were evaluated using scanning electron microscopy, phase formation was studied using X-ray diffraction, and chemical composition was estimated using X-ray fluorescence. As a result, glass foam with hierarchical density.
Keywords: espuma vítrea; agente espumante; porosidade; Hidróxido de sódio; Dióxido de titânio; vidro reciclado; foam glass; foaming glass; porosity; Sodium hydroxide; Titanium dioxide; recycled glass; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA